A new approach to manage the connection queue - Nicolas Ostler; Furong Li; Lewis Dale (IET Smart Grid)
Abstract The connection queue has seen unparalleled growth over the last 24 months. With the record number of connection agreement applications representing a pivotal time for system development as we drive investment that will enable us to transition into an electrified future. The authors look to address challenges posed to the connection queue through congestion management‐based techniques. Conducting a top down approach, the authors first visualise the state of the queue. Observing highest growth in pure storage based applications distributed close to traditional load centres, followed by wind projects along the East Coast and Northern Scotland. Supporting close analysis is performed on the representative B6 boundary. The authors compare methodologies, validate a process for the attribution of congestion cost and quantify the value of investment given by unit power changes. Finding that most significant value of investment in storage lies in the Southeast of England and the North of Scotland. This reflects the identified current state of constraint and most efficient current utilisation of available capacity. These approaches have been aligned with current system thinking and progress towards a new industry data sharing standard, forming strategy by which we look to transition the energy system and country into a decarbonised future.